Una caratterizzazione delle coniche di PG (2,q) - Stefania Ferri (Ratio Mathematica, 1996)
We prove that a k-sct K of PG(2,q), with k 5 mt, of class 10, m, n], , with respect to the lines, such that for each point of K meets, at the most, a m-sccant line, is a conic.